Respuesta :
Answer:
A. -5/4, 9
Step-by-step explanation:
The solution is in the picture
![Ver imagen ernest725](https://us-static.z-dn.net/files/ddd/78cdce81e1525da27c0339b6e5f934c4.jpg)
Answer:
A
Step-by-step explanation:
Given
4m² - 31m - 45 = 0
Consider the factors of the product of the coefficient of the m² term and the constant term which sum to give the coefficient of the m- term
product = 4 × - 45 = - 180 and sum = - 31
The factors are - 36 and + 5
Use these factors to split the m- term
4m² - 36m + 5m - 45 = 0 ( factor the first/second and third/fourth terms )
4m(m - 9) + 5(m - 9) = 0 ← factor out (m - 9) from each term
(m - 9)(4m + 5) = 0
Equate each factor to zero and solve for m
m - 9 = 0 ⇒ m = 9
4m + 5 = 0 ⇒ 4m = - 5 ⇒ m = - [tex]\frac{5}{4}[/tex]